Morphogenesis of the tumor patterns - Elena Izquierdo-Kulich; José Manuel Nieto-Villar (Mathematical Biosciences and Engineering, 2008)
The mathematical modeling of tumor growth allows us to describethe most important regularities of these systems. A stochastic model, basedon the most important processes that take place at the level of individual cells,is proposed to predict the dynamical behavior of the expected radius of thetumor and its fractal dimension. It was found that the tumor has a characteristicfractal dimension, which contains the necessary information to predictthe tumor growth until it reaches a stationary state. This fractal dimensionis distorted by the effects of external fluctuations. The model predicts a phenomenonwhich indicates stochastic resonance when the multiplicative and theadditive noise are correlated.